Quality of Goat Milk Cheese with Addition of Rice Bran oil Ripened Using Lactobacillus casei and Streptococcus thermophilus - Nurliyani Nurliyani; Indratiningsih Indratiningsih; Widodo Widodo; Endang Wahyuni (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2020)
This study aimed to determine the effect of rice bran oil (RBO) addition on the microbiological, chemical, physical and sensory qualities of goat milk cheese ripened using  Lactobacillus casei FNCC 0090 and Streptococcus thermophilus FNCC 0040. Cheese was prepared from goat's milk with a starter of Lactobacillus casei and Streptococcus thermophilus and rennet as coagulant. Cheese was divided into four groups: 1) ripened cheese without RBO stored for 0 d, 2) ripened  cheese without RBO stored for 30 d, 3) ripened cheese + RBO stored for 0 d and  4) ripened cheese + RBO stored for 30 d. The results showed that the addition of RBO and ripening did not affect on the total number of lactic acid bacteria (LAB) of the cheese (their total number were in the range of 2.60-4.21x107 CFU/g). The acidity of cheese without RBO after ripening was higher (p<0.05) than without  ripening. Therefore, the pH value of cheese with the addition of RBO was higher than the cheese without RBO. The addition of RBO had no effect on moisture content of cheese, but the moisture content decreased (p<0.05) after ripening. Meanwhile, the addition of RBO could reduce their soluble protein. Cheese added with RBO had a harder texture (p<0.05) than cheese without RBO. Sensory quality of cheese was not influenced  by the addition of RBO, but the saltiness of cheese with RBO was higher than without RBO and had no bitter in  taste. In conclusion, RBO had no negative effect on the flavor and acceptability of the cheese and the growth of  LAB, could increase cheese hardness, but could decrease the acidity and soluble protein in the cheese. However, the cheese with the addition of RBO ripened using starter consisting of Lactobacillus casei FNCC 0090 and Streptococcus thermophilus FNCC 0040 could be potentially classified as probiotic cheese which is beneficial for health.